Networked Scholarship and Motivations for Social Media use in Scholarly Communication - Manca, Stefania; Ranieri, Maria (International Review of Research in Open and Distributed Learning, 2017)
Research on scholars’ use of social media suggests that these sites are increasingly being used to enhance scholarly communication by strengthening relationships, facilitating collaboration among peers, publishing and sharing research products, and discussing research topics in open and public formats. However, very few studies have investigated perceptions and attitudes towards social media use for scholarly communication of large cohorts of scholars at national level. This study investigates the reasons for using social media sites for scholarly communication among a large sample of Italian university scholars (N=6139) with the aim of analysing what factors mainly affect these attitudes. The motivations for using social media were analysed in connection with frequency of use and factors like gender, age, years of teaching, academic title, and disciplinary field. The results point out that for the most used tools the influence of the variables examined was higher in shaping scholars’ motivations. In fact, frequency of use, age, years of teaching, and disciplinary field were found to be relevant factors especially for LinkedIn and ResearchGate-Academia.edu, while gender and academic title seemed to have a limited impact on scholars’ motivations for all social media sites considered in the study. Considerations for future research are provided along with limitations of the study.